Коло юридичних осіб, що потребують спеціальних правил банкрутства - Стефанів, Т.В. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Статья посвящена одному з ключевых элементов рынковой экономики - институту банкротства, а именно: вопросов усовершенствования и розширения круга юридических лиц, которым необходимы специальные правила банкротства. Автор статьи делает вывод о том, что данный круг юридических лиц с учетом их социальной и економической значимосте в государстве должен быть расширен. Доказывается необходимость принятия Закона «Об особенностях несостоятельности (банкротства) субьектов естественных монополий топливно-энергетического комплекса», Закона «О несостоятельности (банкротстве) кредитных организаций», которые существенно дополнили б раздел VI Закона Украины «О восстановлении платежеспособности должника или признании его банкротом» и решило б ряд проблем в этой сфере. The article is dedicated to one of the key elements of market economy - the institution of bankruptcy, especially to the question of improving and extension of the categories ofjuridical persons who require special regulations of bankruptcy. The author of the article makes a conclusion that the list of such juridical persons would be expanded, taking into consideration it's social and economic importance. It is also proposed to complete it by the following categories: state enterprises and non-commercial institutions. According to the author it will be poitful to adopt the following laws: «Peculiarities of insolvency of the subjects of natural monopolies in the fuel and power complex» and the law «About the bankruptcy of credit organisations». These laws will considerably supplement the law of Ukraine «About the restoration of debtors paying capacity or confessing it's bankruptcy», in particular issue IV It will be also determined the urgent problems concerning this sphere.